Русские падежи сквозь призму валентностиRussian cases through the prism of valency - Lönngren, Lennart (Poljarnyj vestnik, 2013)
The article is a fairly extensive description of the functions of cases in Russian, based on valency theory. Pervadingly a distinction is made between signs occypying nodes in the corresponding graph, and "node-less" signs. Each Russian case can function in both capacities, except the prepositional case, which is always nodeless. In addition to the traditional six cases, two more are postulated, namely the agreement case and the indeterminate case.